Just one damned thing after another - Taylor, Jodi (Taylor, Jodi. Chronicles of St. Mary's, 2016)
Madeline "Max" Maxwell has stumbled on the dream of a lifetime: a career as a time-traveling historian with St. Mary's Institute of Historical Research. The researchers are under strict orders to observe only--no interaction with the locals is allowed. But from her first mission rescuing artifacts from the Great Library of Alexandria, Max realized that time travel is a dangerous activity and that history--and other historians--will go to elaborate lengths to protect themselves.--